Effect of prior cold work on age hardening of Cu-4Ti-1Cr alloy - Markandeya R.; Nagarjuna S.; Sarma D.S. (My University, 2025)
The influence of cold rolling to 50, 75 and 90% reduction on the age hardening behaviour of Cu-4Ti-1Cr alloy has been investigated by hardness and tensile tests and optical as well as transmission electron microscopy. Hardness of Cu-4Ti-1Cr alloy increased from 222 Hv in solution treated condition to 416 Hv with 90% cold work and peak aging. Cold deformation reduced the peak aging temperature from 450 °C for the undeformed alloy to 400 °C for cold deformed alloys. The yield strength (YS) and ultimate tensile strength (UTS) of the alloy with 90% cold work followed by peak aging at 400 °C were found to be 1165 and 1248 MPa, respectively. The microstructure of the deformed alloy exhibited elongated grains and deformation bands. The maximum strength on peak aging was obtained due to precipitation of ordered, metastable and coherent β1, Cu4Ti phase in addition to high dislocation density and deformation twins. Overageing of the alloy resulted in reduced hardness and strength due to the formation of incoherent and equilibrium β, Cu3Ti phase in the form of cellular structure. However, the morphology of the discontinuous precipitation was changed to globular shape with high deformation. © 2005 Elsevier B.V. All rights reserved.